The five self-harm behavior groupings measure: empirical and thematic data from a novel comprehensive self-harm assessment - Liljedahl, Sophie I.; Daukantaitė, Daiva; Kleindienst, Nikolaus; Wångby-Lundh, Margit; Westling, Sofie (Frontiers in Psychiatry, 2023)
The Five Self-Harm Behavior Groupings Measure (5S-HM) is a novel assessment that evaluates behaviours which may go undetected by existing measures. Self-harm is formulated across directness and lethality spectra, including under-studied behaviours such as indirect self-harm, harmful self-neglect and sexual self-harm. Aims of the study were to: 1) Empirically evaluate the 5S-HM; 2) To determine whether the 5S-HM generates relevant new information with respect to the forms and functions given by participants for self-harm within a clinical sample; 3. To test the utility and novel contributions of the Unified Model of Self-Harm and the 5S-HM by extension. Data were collected from N=199 individuals (Mage = 29.98, SD = 8.41, 86.4% female), receiving specialized evidence-based treatments for self-harm, borderline personality disorder or eating disorders. Construct validity was determined via Spearman correlations, and internal consistency was established from Cronbach’s alpha. Test-retest reliability on a subsample of n= 24, tested 14 days after Time 1 was supported by a good intraclass correlation (.68). Inductive thematic analysis was used to analyze and interpret qualitative data on reasons, forms and functions participants reported in relation to self-harm following Braun and Clarke’s analytic guidelines. Thematic mapping was used to summarize qualitative data. Internal consistency (Cronbach’s alpha = .75) was acceptable to good, as was construct validity comparing the 5S-HM total score to two validated self-harm measures (rho=.40, p<.01; rho=.26, p<.01). A thematic map depicting antecedents and consequences of self-harm over time suggests that self-harm is initiated by negative emotional states and self-intolerance. Novel findings in relation to sexual self-harm indicated that reasons for these behaviours were either to improve or worsen one’s situation through being hurt by someone else. The empirical analyses of the 5S-HM demonstrate that it is a robust measure for use in clinical and research settings. Thematic analyses proposed explanations for why self-harm behaviours are initiated and how they are reinforced over time. Sexual self-harm in particular requires further careful study.